'Malignant' macroscopic appearance of an inflammatory testicular lesion--a reminder for surgeons. Issue 666 (April 1981) - Sternberg, A.; Mor, C.; Servadio, C.; Reiss, R.
Abstract : Inflammatory changes in the tunica vaginalis testis may assume a misleading appearance which is highly suggestive of malignancy. Obviously, histological examination is crucial for establishing the corrent diagnosis. This phenomenon has been described in texts dealing specifically with testicular pathology, but is not emphasized in standard text books of urology, surgery or pathology. An illustrative case serves as the basis for discussing this entity, for the purpose of familiarizing it to surgeons, urologists and pathologists who are yet unaware of it.